2011
DOI: 10.1074/jbc.m110.178780
|View full text |Cite
|
Sign up to set email alerts
|

A Novel KRAB Domain-containing Zinc Finger Transcription Factor ZNF431 Directly Represses Patched1 Transcription

Abstract: Krüppel-like zinc finger transcription factors compose the largest transcription factor family in the mammalian genome. However, the functions for the majority of these transcription factors as well as their in vivo downstream targets are not clear. We have functionally characterized a novel KRAB domain zinc finger transcription factor ZNF431 using both in vitro and in vivo assays. ZNF431 is a nuclear transcriptional repressor whose repressive activity depends on its association with HDAC1 and -2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…These transcription factors are involved in the regulation of cell differentiation, proliferation, apoptosis and neoplastic transformation[4749]. A recent report implicates ZNF431 in controlling both Ptch1 basal expression and cellular response to Hedgehog signaling, which suggests a role for this transcription factor during developmental stages[50]. …”
Section: Discussionmentioning
confidence: 99%
“…These transcription factors are involved in the regulation of cell differentiation, proliferation, apoptosis and neoplastic transformation[4749]. A recent report implicates ZNF431 in controlling both Ptch1 basal expression and cellular response to Hedgehog signaling, which suggests a role for this transcription factor during developmental stages[50]. …”
Section: Discussionmentioning
confidence: 99%
“…It is thought that KRAB-ZFPs bind to DNA and recruit corepressors such as KAP1, HDACs, HP1, and Setdb1 to silence gene expression from target promoters (Urrutia 2003). Recently, it has been shown that ZNF431 (the human homolog of Zfp431) directly represses expression of Patched 1, a target of Hh signaling (He et al 2011). It can be anticipated that Zfp157 modulates the expression of Stat6 and Gata-3 target genes in the subpopulation of alveolar cells in which these transcription factors are expressed.…”
Section: Zfp157 Is a Member Of A Family Of Transcriptional Repressorsmentioning
confidence: 99%
“…C and 2D ), we found several genes coding for zinc finger proteins such as ZNF92 , ZNF107 and ZNF430 , not previously reported as being affected in the context of PMF. Moreover, HMGXB4 and ZNF431 , negative regulators of WNT and Hedgehog (Hh) pathways, respectively, were also found in the deleted signature. Finally, worth of notice is YTHDC1 , a splicing factor whose loss has been recently associated with poor overall and disease‐specific survival in endometrial cancer .…”
Section: Resultsmentioning
confidence: 99%